Religious truth and religious diversity - Hilberg, Nathan S. (American university studies / 7, 2009)
Introduction -- Overview of religious realism -- A realist interpretation of religious diversity -- Religious exclusivism : the problem of being arbitrary -- Overview of religious irrealism -- Religious non-realism : neither realist nor anti-realist -- Religious non-realism pushed beyond its limits -- Conclusion